Legume-based rotation alters soil eukaryotic community and improves soil multifunctionality - Tingwei Meng; Yi Fan; Yiheng Tao; Yi Wu; Shuang Pang; Wei Yang; Xiaoyu Guo; Ximei Zhang (Annals of Microbiology)
Abstract Background Legume-based rotation modulates soil microbial communities, which are critical to soil health and sustainable agriculture. However, current researches primarily focus on the effects of legume-based rotation on the bacterial community, leaving eukaryotic responses to this rotation poorly characterized. Methods We analyzed soil eukaryotic communities via 18 S rRNA sequencing in a Mollisol region under maize monoculture versus maize-soybean rotation, integrating soil physicochemical data and network analysis to elucidate rotation-driven eukaryotic assembly patterns. Results Maize-soybean rotation increased fungal and protistan richness by 53.04% and 23.80%, respectively, compared to those in the maize continuous cropping system, while the nematode was not sensitive. Maize-soybean rotation significantly altered fungal and protistan community compositions, increasing the relative abundances of Ascomycota (from 35.79 to 58.51%) and Alveolata (from 13.80 to 18.06%), respectively. Deterministic processes governed these shifts, with soil total carbon driving fungal richness and moisture regulating protistan β-diversity. Reduced environmental filtering under maize-soybean rotation enhanced the richness and network complexity of fungi and protists. Structural equation modeling (SEM) analysis revealed that the maize-soybean rotation improved soil multifunctionality by increasing fungal richness and complicating protistan community structure. Conclusions Our study highlights the pivotal role of fungal diversity and protistan community structure in maintaining soil function under legume-based rotation, providing guidance for agricultural management practice and global sustainable crop production.